2021
DOI: 10.1186/s12985-021-01678-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-viral and pro-inflammatory functions of Toll-like receptors during gamma-herpesvirus infections

Abstract: Toll-like receptors (TLRs) control anti-viral responses both directly in infected cells and in responding cells of the immune systems. Therefore, they are crucial for responses against the oncogenic γ-herpesviruses Epstein-Barr virus and Kaposi’s sarcoma-associated herpesvirus and the related murine virus MHV68, which directly infect immune system cells. However, since these viruses also cause lifelong persistent infections, TLRs may also be involved in modulation of inflammation during latent infection and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Pathway analysis also showed distinct regulations by vitamin D of several MAPK, TLR and interleukin pathways in naive and memory B-cells. In naive B-cells, we found that vitamin D treatment down-regulates interleukin-1 signaling and TLR 1/2 and TLR9 pathways known to stimulate NF-κB signaling (32). NF-κB, MAP kinase, IRF7, and PI3 kinase pathways are known to be stimulated via latent membrane protein 1 (LMP1), a mechanism favoring B-cell immortalization during chronic EBV infection (33).…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis also showed distinct regulations by vitamin D of several MAPK, TLR and interleukin pathways in naive and memory B-cells. In naive B-cells, we found that vitamin D treatment down-regulates interleukin-1 signaling and TLR 1/2 and TLR9 pathways known to stimulate NF-κB signaling (32). NF-κB, MAP kinase, IRF7, and PI3 kinase pathways are known to be stimulated via latent membrane protein 1 (LMP1), a mechanism favoring B-cell immortalization during chronic EBV infection (33).…”
Section: Discussionmentioning
confidence: 99%
“…In the scenario of the primary EBV infection, TLRs assume a crucial function by facilitating the initial identification of the virus within innate immune cells ( 110 ). For example, TLR9 recognizes EBV nucleic acids and activates signaling pathways that lead to the production of pro-inflammatory cytokines, such as type I interferon (IFN-I) or transforming growth factor (TGF), which triggers the antiviral immune response ( 111 ). Conversely, EBV employs cunning tactics to slip through the notice of these PRRs, masterfully reshaping the immune response to its advantage ( Figure 2 ).…”
Section: Invisible Enemy: Hiding From the Innate Immune Systemmentioning
confidence: 99%
“…EBV can reduce TLR expression and/or signal transduction to escape cellular immune responses to TLR activation [ 67 ]. Fathallah et al found that the EBV oncoprotein LMP1 is a strong inhibitor of TLR9 transcription, and its overexpression regulates NF-κB pathway activation, thereby reducing TLR9 promoter activity and its mRNA and protein expression levels [ 68 ].…”
Section: The Interaction Of the Immune System And Ebvmentioning
confidence: 99%